(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article explores the theoretical and methodological foundations of integrating history education with social sciences and humanities such as philosophy, sociology, cultural studies, and psychology. The role of interdisciplinary connections in the development of historical thinking and methods of forming students’ multifaceted approach to historical events are analyzed. During the research, effective ways of analyzing historical processes based on modern pedagogical technologies and cognitive approaches are indicated.